A Study of Forward Osmosis Using Various Drawing Agent - A. Al-Hemiri, Adil; O. Sharil, Adil; Hussein, Mustrfa (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
This research was aimed to study the osmotic efficiency of the draw solutions and the factors affecting the performance of forward osmosis process : The draw solutions used were magnesium sulfate hydrate (MgSO4.7H2O) pojtassium chloride (KCL), calcium chloride (CaCl2) and ammonium bicarbonate (NH4HCO3). It was found that water flux increases with increasing draw solution concentration, and feed solution flow rate and decreases with increasing draw solution flow rate and feed solution concentration. And also found that the efficiency of the draw solutions is in the following order:CaCl2> KCI > NH4HCO3> MgSO4.7H2O